Enhanced energy deposition efficiency of glow discharge electron beams for metal surface treatment - Rocca, Jorge J., author; Etcheverry, Javier I., author; Martínez, Oscar E., author; Cesa, Yanina, author; Mingolo, Nélida, author; IEEE, publisher (Colorado State University. Libraries, 2000)
The energy deposition efficiency and focal spot dynamics of electron beams produced by pulsed cold-cathode high-voltage glow discharges for metal surface treatment are investigated for two different cathode geometries. A concave cathode geometry in which the focusing is dominated by the convergence of the electric field lines in the cathode fall region is compared with a flat cathode in which the focusing is exclusively caused by the self-generated magnetic field. Results of the treatment of AISI 4140 carbon steel samples show that the concave cathode geometry significantly increases the efficiency, reduces the threshold power necessary for melting, and is less sensitive to variations in the discharge parameters and sample position. The results of numerical modeling indicate that the observed increase in efficiency is caused by the longer persistence of the focal spot on the sample. The model can be used to predict the discharge parameters required for a desired treatment.
Keywords: glow discharge; electron gun; surface treatment